Pasture-based Livestock Identification by Coordenated UAVs - Cavalcanti, Millena; Olivieri, Bruno; Lamenza, Thiago; Endler, Markus (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2024: Anais do XLII Simpósio Brasileiro de Redes de Computadores e Sistemas DistribuídosDO - 10.5753/sbrc.2024.1285, 2024)
The increase and improvement of meat production over the last decade is certainly a result of the growing adoption of Information Technology in livestock farming. Precision livestock farming represents a prominent strategy to deliver notable quantitative and qualitative headways and enhance animal welfare and resource management. When managing free-ranging cattle on pasture, there is the problem of identifying, counting and monitoring cattle effectively, despite the extent of the pasture and the dispersal of the animals. Using swarms of Unmanned Aerial Vehicles (UAVs) as cattle data collectors (through readings of RFID ear tags), this work proposes an identification and counting approach to enhance UAV collaboration and routing of the collected data for improved area coverage. The approach integrates coverage algorithms to inventory cattle into a farm management system using some UAVs as the lastmile communication agent. A simulated environment considering pastures of small and medium-sized farms with varying concentrations of cattle supports simulations with an accuracy of 89% for a 16-minute tracking mission, reaching 100% effectiveness for cattle concentration rate within the average density of Brazilian farms.